Environmental friendliness of traditional fishing gear in the northern coastal waters of East Java, Indonesia - Rahmany, Cindy Ananda; Samudra, Muhammad Farhan Satya Bintang; Wijaya, Amelia Rachma; Ramadhan, Yusril Ilhami; Perdanawati, Rizqi Abdi (UIN Sunan Ampel Surabaya, 2025)
The northern waters of East Java are classified as semi-enclosed marine areas, characterized by relatively mild wave activity and shallow depths. Seasonal monsoon winds significantly influence ocean currents in this region, creating favorable conditions for the exploitation of coastal and marine resources. Communities living in these coastal areas exhibit a high socio-economic dependency on marine ecosystems. This study aims to assess the types of fishing gear used by communities along the northern coast of East Java, focusing on gear design, construction materials, catch composition, and environmental sustainability. The findings reveal that fishermen in Surabaya City and Sidoarjo Regency primarily utilize traditional fishing gear such as nets, traps, rods, and region-specific tools locally known as serok, sonder, cager, nyatak, pancalan, and garit. An environmental friendliness assessment based on FAO (1995) criteria yielded high scores: gillnets (28.21), waring nets (31.25), garit (31.74), and traps/bubu (33.26). These results place all gear types within the